Dabigatran‐induced esophagitis with full circumferential blue pigmentation - Tomonori Araki; Kohei Hayashi; Yuki Sonoda; Takuya Honda; Yoshifumi Imamura; Yuji Koide; Hisayuki Hamada; Kazuhiko Nakao (DEN Open)
Abstract Dabigatran is a useful and widely used drug for stroke prevention in patients with atrial fibrillation. However, it has been reported to cause esophagitis. Herein, we report the case of a 77‐year‐old man with dabigatran‐induced esophagitis with blue pigmentation, which is known to be a rare adverse effect. The patient presented to our hospital with a tightness of the chest and anorexia. Computed tomography revealed a thickening of the entire esophageal wall, with an upper esophageal predominance. Esophagogastroduodenoscopy was performed, which showed that the cervical and upper thoracic esophagus had blue pigmentation with edematous changes, partial narrowing, and longitudinal sloping. We replaced dabigatran with edoxaban, a similar anticoagulation medication. The patient was closely monitored for 1 month after switching to edoxaban. The follow‐up esophagogastroduodenoscopy showed marked improvements, revealing resolution of the bluish discoloration and edematous changes, and the patient's complaints regarding the tightness of the chest and anorexia were also resolved. It is important to recognize that such side effects can occur with dabigatran, a drug that is frequently used in daily practice. Considering the fact that strong edematous changes can cause indigo carmine pigmentation associated with dabigatran stagnation, we recommend switching to another anticoagulant if esophagitis occurs during dabigatran administration.